The Relationship of Women's Knowledge and Attitudes with Pap Smear Examination at Bhayangkara Hospital Makassar - Ekayanti, Ekayanti (Hasanuddin Medan, 2022)
According to WHO (2011), cervical cancer is one of the leading health problems for women throughout the world with an estimated 529,409 new cases and around eighty-six percent (86%) in developing countries. In Indonesia, it is estimated that every day 40-45 new cases appear, 20-25 people die, meaning that every 1 hour it is estimated that 1 woman dies due to cervical cancer. The aim of the research was to determine the relationship between women's knowledge and attitudes with pap smear examinations at Bhayangkara Hospital Makassar. This research uses analytical research methods. The population is women who come for check-ups at Bhayangkara Hospital Makassar Family Planning Polyclinic. The sample studied was 39 people using accidental sampling technique. The research started from March 7 to April 7 2016. Data was collected using a questionnaire and then statistical analysis was carried out using the chi square test with the alternative Fisher's exact test with a significance level of ? < 0.05. The research results showed that the majority of respondents had insufficient knowledge, namely 29 people (74.4%). Based on attitudes, the majority of respondents with a negative attitude were 32 people (82.1%), and the majority did not have a pap smear, namely 27 people (69.2%). The results of the Fisher's exact test obtained a value of p = 0.004 < 0.05, and p = 0.002 < 0.05. Based on the research results, it was concluded that there was a relationship between women's knowledge and pap smear examinations, and there was a relationship between women's attitudes and pap smear examinations. It is recommended that health workers, considering the low level of public behavior regarding the importance of Pap smears, need to take several steps to increase people's knowledge, attitudes and behavior regarding the importance of Pap smears.